Peran Pengendalian Intern Salah Satu Faktor Yang Mempengaruhi Pencegahan Fraud - Karolina, Puspa Erika; Ladewi, Yuhanis; Aprianto, Aprianto; Gantino, Rilla (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
This study was conducted to answer the existing problem, namely how much influence the implementation of internal control has on fraud prevention (Survey on the Lahat Regency Regional Work Unit). The aim is to determine the effect of the implementation of internal control on fraud prevention (Survey on the Lahat Regency Regional Work Unit). This research uses associative and descriptive research types. The place of research was carried out in the Lahat Regency Regional Work Unit. The variables used are the internal control system and fraud prevention. The data used are primary and secondary data. Data collection techniques used in this study were interviews, questionnaires, and documentation. The sampling method used simple random sampling. Data analysis methods that will be used in this research are quantitative and qualitative. The analysis technique used is simple linear regression analysis. Then proceed to test the hypothesis (t test). The data analysis technique in this study was assisted by the Statistical Program For Special Science (SPSS). The results of the normality test can be concluded that the normal P-P plot graph shows that the regression model is feasible to use because it meets the assumption of normality. From the heteroscedasticity test, it can be concluded that there is no heteroscedasticity and no autocorrelation. The results of the analysis show that internal control has a significant influence on fraud prevention in the Lahat Regency Regional Work Unit. From the results of existing research and discussion, the conclusion in this study is that internal control has a significant influence on fraud prevention